(3GdHdOGf GdfGejI h bVGjGgG GdedMI (B/s - (3Lhcha,GScfOha,SJjHGfha s; (3GdjGS TGgjfs ((3ehSch (B:s (3OGQ GdJbOe ,s, 1978)
(3MQcI GdJMQQ GdhWfj h GdYgO GdeYGUQ (B,(3Gdbhi GdeMQcI aj KhQGJ GdJMQQ(B,(3GdGSJYeGQ GdMGdj(B,(3bVjI GdGSJbdGd GdGbJUGOj(B,(3MJejI GdJMhjdGJ GdGLJeGYjI (B,(3GNJjGQ GdWQjb(B,(3GdJjGQGJ GdGTJQGcjI aj GdHdOGf GdfGejI h GdGTJQGcjI GdYdejI (B,(3GdbhejI h GdGeejI(B, (3MQcI GdJMQQ GdhWfj h GdGTJQGcjI GdYGdejIs
(3eJQLes
Keywords: (3GdOhd GdfGejIs